Optimal control of the process of fertilizer granulating in fluidized bed - Новиков, А. Н.; Корниенко, Б. Я. (Proceedings of National Aviation University (archive), 1999)
Given are the results of system synthesis of the optimal control of the process of fertilizer granulating in fluidized bed. Obtained is the law of control of using up the solution and optimal distribution of temperatures. Given are the results of calculation of the bed temperature at corresponding control influence